Efektivitas Pelayanan Pendaftaran Administrasi Kependudukan Melalui Sistem Layanan Online Dukcapil Depok Bersih Mudah Dan Lancar (Silondo Bermula) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Depok - ‘Aisy, Rofiifah Rohadatul; Sugiarti, Cucu; Rizki, Mochamad Faizal (Peneliti.net, 2025)
The online-based population administration registration service program (Silondo Bermula) is a program designed to facilitate the community and the Depok City Population and Civil Registration Office in population administration registration and civil registration services to the people of Depok City during the covid-19 outbreak. In its implementation, there are still problems such as the lack of face-to-face socialization so that there are still many who do not know and do not understand about the program, causing this online-based population administration registration service program to not run optimally. The method used is a descriptive method with a qualitative approach. Data collection techniques with observation, interviews, and documentation. The results showed that many people's understanding of the online-based population administration registration program (Silondo Bermula) already knew and used it. But there are still many who do not. This is due to the lack of face-to-face socialization by the Depok City Population and Civil Registration Office to all communities who are the main targets of this program. However, community participation in this program is quite good. The completion time of population documents submitted by the community exceeded the estimated time given. The achievement of objectives in the implementation of this program has been achieved because the community and the Depok City Population and Civil Registration Office feel helped by the program innovation. Now the people of Depok City can feel the impact of the real changes caused by this online service program. Many people already know and participate in using the program